Dienogest is as effective as leuprolide acetate in treating the painful symptoms of endometriosis: a 24-week, randomized, multicentre, open-label trial - Strowitzki, Thomas; Marr, J.; Gerlinger, C.; Faustmann, T.; Seitz, C. (Human reproduction, 2010)
Dienogest is a selective progestin that has been investigated in a clinical trial programme for the treatment of endometriosis. The current non-inferiority trial compared the efficacy and safety of dienogest against leuprolide acetate (LA) for treating the pain associated with endometriosis.Patients with confirmed endometriosis were randomized to treatment with dienogest (2 mg/day, orally) or LA (3.75 mg, depot i.m. injection, every 4 weeks) for 24 weeks. The primary efficacy variable was absolute change in pelvic pain from baseline to end of treatment, assessed by visual analogue scale (VAS). Safety variables included adverse event profile, laboratory parameters, bone mineral density (BMD), bone markers and bleeding patterns.A total of 252 women were randomized to treatment with dienogest (n = 124) or LA (n = 128); 87.9 and 93.8% of the respective groups completed the trial. Absolute reductions in VAS score from baseline to Week 24 were 47.5 mm with dienogest and 46.0 mm with LA, demonstrating the equivalence of dienogest relative to LA. Hypoestrogenic effects (e.g. hot flushes) were reported less frequently in the dienogest group. As expected, bleeding episodes were suppressed less with dienogest than with LA. Changes in mean lumbar BMD between screening and final visit were +0.25% with dienogest and -4.04% with LA subgroups (P = 0.0003). Markers of bone resorption increased with LA but not dienogest.Dienogest 2 mg/day orally demonstrated equivalent efficacy to depot LA at standard dose in relieving the pain associated with endometriosis, although offering advantages in safety and tolerability.
Gesehen am 01.09.2023